FOTOTERAPI PADA PASIEN GERIATRI: APAKAH BERBEDA DENGAN PASIEN DEWASA? (PERDOSKI, 2020)
The global rise in life expectancy as an indicator of the development goal leads to a proportionate increase in geriatric population. This condition poses a specific challenge to our healthcare system. Considering the geriatric patients’ vulnerability, healthcare provider has to provide highly effective and safe therapeutic options. Phototherapy is a treatment modality utilizing the biological effect of the ultraviolet radiation to the immune system and skin cells. It is proven to improve many skin diseases. Phototherapy can be applied on its own (ultraviolet A and B) or in combination with psoralen (PUVA), which is known as photochemotherapy. The application in geriatric patients requires special considerations: differences in skin structures and physiology, photoadaptation, physical and cognitive impairments. Despite the similar indications in adults, proper adjustments and follow-up must be applied. Several strategical plans are needed to ensure that phototherapy is an accessible therapeutic option. Currently, there are no well-established phototherapy guidelines for geriatric patients. A lower starting dose, combined with a slow incremental rate, may prevent the occurrence of adverse events. Previous studies have shown that phototherapy is considered as an effective and safe procedure to improve many skin diseases in geriatric patients.